Bovine Dermal Matrix as Coverage of Facial Nerve Grafts - E. A. Kappos; P. E. Engels; R. Wettstein; D. J. Schaefer; D. F. Kalbermatten (Case Reports in Medicine)
Introduction. Soft tissue defects over functional structures represent a challenge for the reconstructive surgeon. Often complex, reconstructive procedures are required. Occasionally, elderly or sick patients do not qualify for these extensive procedures. Case. We present the case of a 91-year-old lady with large hemifacial defect with exposed bone and nerves after tumor resection. We first performed radical resection including the fascia of the temporalis muscle and the frontal branch of the facial nerve. Due to the moribund elderly patient with a potentially high perioperative risk, we decided against flap reconstruction but to use bovine collagen/elastin matrix and split thickness skin graft. Results. No postoperative complications occurred and STSG and matrix healed uneventfully. Discussion. In selected cases, where complex reconstruction is not appropriate, this procedure can be a safe, easy, and fast alternative for covering soft tissue defects even on wound grounds containing nerve grafts.